Blastomatoid pulmonary carcinosarcoma: A rare case report and review of the literature. Issue 10 (14th August 2018) - Sakane, Tadashi; Okuda, Katsuhiro; Hattori, Hideo; Watanabe, Takuya; Oda, Risa; Tatematsu, Tsutomu; Yokota, Keisuke; Haneda, Hiroshi; Inagaki, Hiroshi; Nakanishi, Ryoichi
Abstract : A 65‐year‐old never‐smoking woman presented to a local hospital, because an abnormal shadow was detected at the right lower lung field by annual chest X‐ray. Computed tomography (CT) revealed a 5‐cm tumor in segment 6 of her right lung and an enlarged subcarinal lymph node, suggesting metastasis. The lung tumor was diagnosed as adenocarcinoma by a CT‐guided percutaneous needle biopsy. She was referred to our hospital and underwent right lower lobectomy with lymph node dissection (ND2a‐2). A histopathological examination of the tumor showed a biphasic proliferation made of carcinomatous and sarcomatous components. The carcinomatous component consisted of glandular structures of atypical cells that possessed chromatin‐rich nuclear and clear cytoplasm, confirming high‐grade fetal adenocarcinoma. The sarcomatous component consisted of immature spindle cells that differentiated into chondrosarcoma. Immunohistochemically, the glandular structures expressed membranous beta‐catenin, and the ultimate diagnosis was blastomatoid variant of pulmonary carcinosarcoma. She received four courses of cisplatin plus vinorelbine as adjuvant chemotherapy and remained alive with neither recurrence nor distant metastasis at two and a half years after the operation. We experienced a rare case of blastomatoid pulmonary carcinoasarcoma.